2005
DOI: 10.1111/j.1365-2133.2005.06587.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aetiology and pathogenesis of basal cell carcinoma

Abstract: Summary Recent insights into the cell biology of the epidermis and its appendages are transforming our understanding of the pathogenesis of basal cell carcinoma (BCC). The significant progress that has been made warrants a comprehensive review of the molecular and cellular pathology of BCC. The items addressed include environmental and genetic risk factors, the biology of the putative precursor cell(s), and the contribution of aberrations in processes such as apoptosis, cell proliferation, differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
2
24

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 302 publications
(467 reference statements)
2
112
2
24
Order By: Relevance
“…A good substitute for it will exist with the availability of limited primary excision followed by adjuvant therapy using an immunomodulator, a proapoptotic agent and/or a cell-signaling modulator (Tilli et al, 2005;Sekulic et al, 2012;Tang et al, 2012;Macha et al, 2013). This better and novel treatments and tailored drug therapy is regarded the most likely short-term benefit from genetic association studies (Hirschhorn et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A good substitute for it will exist with the availability of limited primary excision followed by adjuvant therapy using an immunomodulator, a proapoptotic agent and/or a cell-signaling modulator (Tilli et al, 2005;Sekulic et al, 2012;Tang et al, 2012;Macha et al, 2013). This better and novel treatments and tailored drug therapy is regarded the most likely short-term benefit from genetic association studies (Hirschhorn et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that TP53 mutations in BCC could be secondary, occurring after the initiation of the tumor. 35 Recent studies on gene TP53 have demonstrated mutations of the "UV signature" type, i.e., predominant conversions of C(C)♦T(T). Thirty-three percent of patients with BCC of Korean origin presented mutations in p53, 36 which attained 50% in Caucasian patients.…”
Section: Protein P53 and The Cell Cycle Inhibitorsmentioning
confidence: 99%
“…BCCs occur most on sun-exposed areas of the body, such as the head and neck (80% of cases). Acute and chronic skin exposure to ultraviolet radiation is supposed to be a crucial factor in the development of skin cancer [9,22]. However, it is not likely that the increased incidence in young persons over time is due to sun exposure alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although mortality rates are low, BCCs may grow per continuitatem and cause severe local destruction. Metastasis occurs in less than 1% [19,22].…”
Section: Introductionmentioning
confidence: 99%